Literary Texts as a Basis of Social Competence Formation in the Foreign Language Learning Process at High Schools - Islamova Tohira Rikhsibayevna (Genius Publishing Group, 2022)
In this article we talk about the use of literary texts for the formation of social competence in the process of learning a foreign language in high schools. A modern professional should be prepared to cross-cultural communication, which goes beyond his professional sphere. Nowadays important is the ability and willingness of the university graduate to communicate with native speakers in everyday life, because personal contacts, human relationships often play a decisive role for the achievement of mutual understanding between different cultures
Keywords: Artistic Text; Socio-Cultural Competence; Rich Vocabulary; Broad-Minded